Host-parasite relationships in paracoccidioidomycosis - Franco, M. (Oxford University Press (OUP), 1987)
A viewpoint of host-parasite relationships in paracoccidioidomycosis is presented. The characteristics of the fungus which are important to the host-parasite interaction are discussed. Aspects of inhibition of mycelium-to-yeast transformation by estrogens acting at receptors on the fungal wall and in the cytoplasm, and the role of polysaccharide components of the cell wall in virulence are reviewed. The natural mechanisms of host defense are also examined, including phagocytosis, complement system, natural-killer cells and genetic control of resistance and susceptibility. Finally, a discussion of granuloma morphogenesis and its relationship to the humoral and cellular anti-P. brasiliensis immune response is presented.
Keywords: complement; cellular immunity; chemotaxis; etiology; fungus; host parasite interaction; human; humoral immunity; natural killer cell; paracoccidioides brasiliensis; phagocytosis; review; south american blastomycosis; Antibodies, Fungal; Complement; Granuloma; Human; Immunity, Cellular; Mitosporic Fungi; Paracoccidioides; Paracoccidioidomycosis; Phagocytosis; Virulence